Analysis of The Implementation of E-Canteen in Creating A Healthy Environment and Guaranteed Nutrition For Children in Indonesia - Andhika Lungguh Perceka; Cahyaning Rini Utami; Hayuti Windha Pagiu; Rahmi Setiawati; Samuel Indrayana (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
ABSTRACT This study is a qualitative study with a descriptive approach, namely an approach that explains the researcher's main objectives with descriptive narratives. There are main narratives described in this study including e-canteen, healthy environment, and good nutrition. The data used in this study are secondary data that the researcher obtained indirectly from books, scientific articles, magazines, and so on. The data obtained was carried out in several stages: collected, selected, reduced, and presented using descriptive narratives. The conclusion in this article show that E-Canteen significantly supports the creation of healthy canteens for the reasons mentioned above. A healthy canteen creates a healthy environment. A healthy canteen environment ensures the availability of good nutrition. Based on this, implementing E-Canteen can indeed create a healthy canteen, a healthy canteen environment, and provide good nutrition.